Establishing semantic interoperability between HL7 v2.x and V3: a Communication Standards Ontology (CSO) - Oemig, Frank; Blobel, Bernd (Journal of Health Informatics, 2011)
Different communication standards in healthcare - esp. HL7 version 2.x and v3 - lack inter- and intra-family compatibility. Bridging between those to establish semantic interoperability using a formal ontology as a mediator in a mapping process has demonstrated that both communication standards have in principle the same underlying architecture. This paper shortly analyses this structure in order to create a communication standards ontology (CSO) based on (basic) formal ontologies (BFO/FO) which is presented thereafter. The paper discusses problems which appeared during the development process and the established solution.